The Importance of Applying the IAS 36 in the Oil and Gas Companies in Syria (A field study) (Journal of Hama University, 2020)
Long-term assets constitute huge amounts in oil and gas companies (in Al-Furat Petroleum Company the value of assets exceeded $ 9 billion as at the end of 2017 according to its financial statements), the book value of these assets need to be reviewed according to IAS 36 "Assets Impairment" and recognize impairment losses when the carrying amount exceeds the recoverable amount. This study came to highlight the importance of applying the IAS 36 in oil and gas companies in Syria when measuring the fair value (recoverable value) of assets, on the other hand highlighting the reality of the application of Standard 36 and the problems of its application in oil and gas companies. The research depends on the descriptive approach through a field study using the questionnaire tool that was distributed to the specialists in the financial departments of the oil and gas companies in Syria, as well as the certified accountants in the Association of Chartered Accountants, the opinions and answers of the members of the research sample were collected, and using the means test (One - Sample t Test) hypotheses were tested.The study concluded that the application of International Accounting Standard No. 36 in oil and gas production companies in Syria is important for the fairness of measuring the value of long-term assets, but the standard is not applied for reasons, the most important of which are the special nature of production sharing agreements in Syria, in addition to the ongoing and unstable changes in oil and gas prices.